Determinants of Halal Tourism of Setu Babakan Jakarta Based on Global Muslim Travel Index and Importance Performance Analysis - Tati Handayani; Sufyati HS; Purwanto Widodo; Pusporini; Anggi Angga Resti (Journal of Islamic Economics and Finance Studies)
Setu Babakan Betawi Cultural Village (PBB) is a betawi-nuanced tourist area developed by the local government of Jakarta and is planned to become a halal tourist destination. This study aims to determine whether the UN Setu Babakan tourist destination implemented Sharia principles as criteria set by the Global Muslim Travel Index (GMTI). To ensure that the analysis results are valid and credible and can be applied by the management of PBB Setu Babakan, research was conducted using primary data with Importance Performance Analysis (IPA). The respondents were tourists at the UN Setu Babakan, Muslim, and over 17 years of age.  The sample consisted of 130 respondents, most of whom were under 20 years of age, high school, and student education. The results showed that according to respondents, services that need to be improved are hotels, SPAs, saunas and massages, travel bureaus and tour guides, many of which are not halal certified, so tourists hesitate to use these services.  These findings are expected to facilitate managers and local governments to develop the right strategy so that visitors to Setu Babakan increase by improving facilities that are lacking.